Endometriosis prevalence and incidence trends in a large population-based study in Catalonia (Spain) from 2009 to 2018. (October 2022) - Medina-Perucha, Laura; Pistillo, Andrea; Raventós, Berta; Jacques-Aviñó, Constanza; Munrós-Feliu, Jordina; Martínez-Bueno, Cristina; Valls-Llobet, Carme; Carmona, Francisco; López-Jiménez, Tomàs; Pujolar-Díaz, Georgina; Flo Arcas, Eva; Berenguera, Anna; et al.
Objective: Endometriosis greatly impacts women's health and quality of life. However, research on the prevalence and incidence of endometriosis remains inconclusive. This study assesses time trends in the prevalence and incidence of endometriosis diagnoses in Catalonia (Spain) from 2009 to 2018, considering differences by age and socioeconomic status. Methods: Population-based cohort study using data from the Information System for Research in Primary Care (SIDIAP) database. Data were included from over 2.4 million women aged 15–55 years between 1 January 2006 and 31 December 2018. Results: A total of 2, 337, 717 women were selected as the incident population; 0.7% had an endometriosis diagnosis. Median (interquartile range) age at diagnosis was 37 (32–43) years. Most women were European (92.3%) and lived in urban areas (73.6%). Overall prevalence of endometriosis consistently increased during the 2009–2018 period, and it was 1.24% in 2018. Trends were the highest for women with less socioeconomic deprivation and for the 35–44 years age group. Median incidence rates were 94.9 (92.6–102.9) per 100, 000 women-years, being the highest in women aged 35–44 years throughout the whole study period. Overall, incidence increased between 2015 and 2017, and plateaued or decreased in 2018. Incidence rates in women from the most deprived and rural areas were lower, although incidence time trends by socioeconomic status were unclear. Conclusion: Healthcare services and public health strategies need to be strengthened to ensure timely endometriosis diagnosis and treatment. Special attention should be given to the most affected populations and the social inequities of health.